Bibliometric Analysis of Research Trends: Sufistic Approach in Character Education in Islamic Boarding Schools (Journal Intellectual Sufism Research (JISR), 2025)
This study aims to conduct a Bibliometric Analysis of scientific literature regarding the Sufistic Approach in Character Education in Pesantren (Islamic Boarding Schools), focusing on publications from the last ten years. The Sufistic Approach, which emphasizes soul purification (tazkiyatun nufūs) and spiritual exercises (riyādhah), is recognized as essential for instilling noble character values such as zuhud (detachment) and tawadhu (humility) in Pesantren. This research employs a quantitative method (Bibliometric Analysis) and a Systematic Review based on the PRISMA guidelines, utilizing VOSviewer for visualization. Search results in the Scopus database reveal an explosive growth in publications related to "Islamic Character Education," increasing nearly tenfold from 2015 to its peak in 2024, confirming this field as a highly relevant and active area of study. Keyword mapping analysis shows the research focus centers on "Character Education," "Islamic Education," and "Islamic Values," clustered around implementation in formal institutions (Pesantren, Islamic Schools), core concepts of moral development (Akhlak, Integration), and the global context (Industrial Revolution 4.0, secularism). The main findings from the in-depth literature analysis consistently validate the Sufistic Approach as an effective framework for addressing contemporary moral and spiritual crises, particularly through the concept of soul purification (Tazkiyah al-Nafs). Tested practical implementation models include the Kiai's leadership strategy, which balances vertical (hablu minallāh) and horizontal (hablu minannās) relationships, and a Quranic story-based learning model. In conclusion, the Sufistic Approach is a relevant and mature strategy for cultivating the Insân Kâmil (the perfect human being) who possesses noble character (akhlak mulia) in the modern era.
Keywords: Character; education; islamic; Sufistic